PENGARUH DISIPLIN KERJA, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL KELURAHAN SE KECAMATAN KOTA KENDAL - Sulaiman Kurdi (Fakultas Ekonomika dan Bisnis Universitas Selamat Sri, 2019)
The purpose of this research is to find out the existence of the influence of discipline, motivation and work environment to the working performance of the Civil Public Servant on the villages of subdistrict Kendal.The study was conducted at Civil Public Servant on the villages of subdistrict Kendal. Method used on this research is quantitative research. This research used data in form questionnaires given to 140 respondents, working as the Civil Public Servant on the villages of subdistrict Kendal.Data analysis used validity test and questionnaire reliability. The result tested using the double regression analysis with parameter test, model precision test and classic assumption. The validity and and reliability test stated that given questionnaires are valid and reliable. Data analysis result shown that discipline variable gave positive score to increase of work’s performance Civil Public Servant on the villages of subdistrict Kendal. The effect of disciplineis 4,056. Motivation variable gave positive score to the increase of work’s performance Civil Public Servant on the villages of subdistrict Kendal. The effect of motivation is 3,815. Mean while work environment variable also gave positive to the increase of work’s performance Civil Public Servant on the villages of subdistrict Kendal. The effect of work environment is 8,375. The F-test and T-test state that discipline, motivation and work environment variable have a significant and positive impact to Civil Public Servant on the villages of subdistric Kendal performance. From the result of analysis, it can be concluded that discipline, motivation and work environment have a positive and significant impact to the performance of Civil Public Servant on the villages of subdistrict Kendal. Really explained that on the three variables is59,1% and the other 40,9% is explained by other variable out of this research